2022
DOI: 10.1021/acs.energyfuels.2c02452
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Quantitation of Phenols in Fuel Extracts by Using Gas Chromatography/Methane Chemical Ionization Triple Quadrupole Mass Spectrometry

Abstract: The ability to detect, characterize, and quantify phenols in aviation fuels is critical as these compounds can negatively affect the storage stability of the fuel. However, some phenols inhibit free-radical autoxidation and hence are beneficial. The development of a method based on gas chromatography coupled with positive-ion-mode methane chemical ionization/triple quadrupole mass spectrometry [GC/(methane CI) QqQ] for the characterization and quantitation of phenols in fuels is reported here. Sixteen phenols,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…The use of CI was shown to prevent fragmentation for natural phenols and PA by using (GC/methane CI) QqQ MS (Guthrie et al, 2022). Protonation [M + H] + was the dominant ionization reactions for natural phenols measured.…”
Section: Prospective Uses Of Mass Spectrometry For the Chemical Analy...mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of CI was shown to prevent fragmentation for natural phenols and PA by using (GC/methane CI) QqQ MS (Guthrie et al, 2022). Protonation [M + H] + was the dominant ionization reactions for natural phenols measured.…”
Section: Prospective Uses Of Mass Spectrometry For the Chemical Analy...mentioning
confidence: 99%
“…The results support similar ionization responses for the phenols. Reprinted (modified) with permission from Guthrie et al (2022). Copyright 2022 American Chemical Society.…”
Section: Prospective Uses Of Mass Spectrometry For the Chemical Analy...mentioning
confidence: 99%
“…Spectra in ECNCI are characterized by limited fragmentation and intense and easily recognizable molecular ions or intense fragment ions. Soft ionization techniques, such as CI, are therefore experiencing renewed interest, demonstrating their advantages and suitability in many applications. , GC-NCI-MS methods have gained significant interest in several fields, ranging from environmental and biological to food, due to the high sensitivity and specificity toward the compounds containing electronegative ions and functional groups. …”
Section: Introductionmentioning
confidence: 99%
“…It was clearly demonstrated that most PFASs tend to be observed using NCI rather than EI or PCI modes. The strong electrophilic character of PFASs is given by the presence of F and the terminal carboxylic group, making these compounds amenable to NCI rather than EI or PCI modes. , The use of NCI as a PFAS detection technique has been described in numerous articles. Considering the high selectivity of CI for halogenated compounds, in this work an ultra-high-performance liquid chromatography (UHPLC) system was coupled with a CI source using the liquid electron ionization (LEI) interface. LEI has been amply demonstrated to allow the proper vaporization of LC-amenable compounds before reaching an under-vacuum ionization source, such as EI or CI.…”
Section: Introductionmentioning
confidence: 99%